Profesor Turun Padang Programme Merdeka Scavenger Hunt fosters spirit of love of country and English through gamification - Noor Azlinda, Zainal Abidin; Jamilah Bebe, Mohamad; Noor Raha, Mohd Radzuan (UMPSA, 2024)
PEKAN, 18 September 2024 - In conjunction with the initiative of Profesor Turun Padang at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), the Centre for Modern Languages (PBM) in collaboration with MELTA Pahang Chapter (MPC) and Persatuan Matahari organised the Merdeka Scavenger Hunt programme held at the Pekan and Gambang campuses on 18 and 19 September 2024.